Efficient principles for heat batteries - R.М. Makhmudov; Z.I.Kholmurodova; Sh.А.Usmonov; S.Sh.Babanazarov (Research Parks Publishing LLC, 2020)
The article deals with the important characteristics required in the design process of short-term and long-term heat batteries, as well as the heat physical properties of heat-collecting materials